THE CONSTRUCTION OF TERRORISM PREVENTION IN LEGAL POLITICS - Bahtiyar Efendi (UNISSULA, 2021)
Terrorism is a criminal act or extraordinary crime that is of concern to the world today, especially in Indonesia. Terrorism that has occurred in Indonesia recently has ideological, historical and political linkages and is part of the dynamics of the strategic environment at the global and regional levels. the approach method uses normative juridical, the results of the study state that the legal politics of eradicating criminal acts of terrorism in Indonesia is a proactive policy and anticipatory step that is based on prudence and is long-term in nature. The use of Act No. 15 of 2003 to regulate the eradication of criminal acts of terrorism is based on the consideration that the occurrence of terrorism in various places has caused material and immaterial losses and caused insecurity for the community. It can be stated that the government's policy to tackle criminal acts of terrorism is by taking legal steps, so that unwanted things can be anticipated.